Participação social: a cultura, a arte e a ciência integradas como ferramentas de regularização fundiária e prevenção de conflitos - BARRADAS, Maria de Lourdes Gomes (2022)
The conventional social participation practices in the Urban Land Regularization processes have always been the target of reflection about the effectiveness of the community participation in their processes and to what extent such participation allowed the interference or the inclusion of the population's wishes in the urbanistic or socio-environmental projects built in them. The present work deals with the analysis of the practices of integration between culture and art articulated to scientific knowledge, as a means of dialogue and social participation in the debate on the Right to the City, developed through participant observation in the several activities we have followed in the different projects executed by the Land Regularization Committee of the Federal University of Pará, which are: Moradia Cidadã Project, My Address Project and Urban Land Regularization Project developed by the Amazon Network Program: to live, live together and preserve, in order to mark the use of multilingual tools as a method to foster social protagonism in the stages of Urban Land Regularization.